Analisis Fiqh Muamalah Terhadap Penerapan Akad Musyarakah Mutanaqisah Dalam Pembiayaan Rumah Di Perbankan Syariah - Sumarni; Aulia, Malika Kesya; Hirmayani, Amanda; Herni; Fatrisia, Anggun Ade; Hasniar (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to analyze the implementation of the Musyarakah Mutanaqishah (MMQ) contract in home financing products of Islamic banking institutions from the perspective of fiqh muamalah. Musyarakah Mutanaqishah represents an innovative Islamic financing scheme that combines partnership principles with gradual transfer of ownership, designed to avoid interest-based transactions in housing finance. This research employs a qualitative method with a normative and conceptual approach by examining classical and contemporary fiqh muamalah literature, the fatwas issued by the National Sharia Council of the Indonesian Ulama Council (DSN-MUI), and relevant regulatory frameworks. The findings indicate that normatively, the Musyarakah Mutanaqishah contract fulfills the essential pillars and conditions of a valid Islamic contract and is legally supported by DSN-MUI Fatwa No. 73/DSN-MUI/XI/2008. The mechanism of joint ownership, payment of ujrah for asset utilization, and gradual transfer of ownership reflects the principles of justice and mutual benefit emphasized in Islamic law. However, practical implementation reveals several challenges, including the potential imbalance of risk allocation and deviations from the ideal partnership model. Therefore, strengthening substantive compliance in the application of Musyarakah Mutanaqishah is essential to ensure alignment with the principles of fiqh muamalah and the objectives of maqashid al-shariah.